Metastatic Merkel cell carcinoma and malignant melanoma in a single sentinel lymph node. (June 2021) - Hamilton, Amanda; Jayaratne, Prasad; Zonta, Mark
Merkel cell carcinoma (MCC) and malignant melanoma are aggressive skin cancers that usually arise in sun-exposed parts of the body. This report describes an 85-year-old man who underwent a wide local excision and sentinel lymph node biopsy for primary MCC and was subsequently found to have metastatic MCC and malignant melanoma within the left inguinal sentinel lymph node. Dual diagnoses of aggressive cutaneous carcinomas, although rare, may become more common in regions of high ultraviolet exposure and an ageing population. Currently, there are no guidelines for treating synchronous MCC and melanoma, however, immunotherapy with PD-1 inhibitors and anti-CTLA-4 receptor antagonists have shown therapeutic effect against these two cancers and should be considered in treatment planning.